1988
DOI: 10.1093/nar/16.20.9557
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a gapped linear duplex DNA intermediate in the replicative cycle of human and simian spumavirases

Abstract: Two forms of linear DNAs have been found in simian (SFV1) and human (HSRV) spumaviruses: a linear duplex unsensitive to nuclease S1 and a sensitive structure with a single-stranded gap. Two nuclease S1 sensitive sites, mapping at the same position for both viruses, have been identified in the gapped structure. Using different molecular subgenomic clones of HSRV as probes in Southern blot analysis, one S1 site was localized in the 3'LTR and the other near the middle of the molecule at about 6.5 kbp from the 5' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 22 publications
7
58
0
Order By: Relevance
“…We have previously demonstrated the existence of linear DNA forms with a gapped region located approximately in the middle of the human spumavirus (HSRV) and simian foamy virus type 1 (SFV1) DNA molecules (Kupiec et al, 1988). This gapped structure was recently confirmed for another SFV, the LK3 isolate (Schweizer et al, 1989).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…We have previously demonstrated the existence of linear DNA forms with a gapped region located approximately in the middle of the human spumavirus (HSRV) and simian foamy virus type 1 (SFV1) DNA molecules (Kupiec et al, 1988). This gapped structure was recently confirmed for another SFV, the LK3 isolate (Schweizer et al, 1989).…”
Section: Introductionmentioning
confidence: 85%
“…DNA was digested with nuclease S1, or heatdenatured as described previously (Kupiec et al, 1988), or HinpIrestricted according to the conditions recommended by the supplier (Biolabs). Southern blots were performed on agarose gels using nitrocellulose.…”
Section: Methodsmentioning
confidence: 99%
“…Visna and HIV-1, and human/simian spumaviruses as well, contain an exact copy of their respective PPTs in pol [110,111]. In the pre-integration complexes of these viruses, a plusstrand gap corresponding to a second site of plus-strand initiation has been detected at this central PPT (cPPT) [105,106,[112][113][114][115][116][117]. The net outcome is that the plus strand of the PIC contains two discrete half-genomic DNA segments.…”
Section: Mechanisms Of Lentiviral Nuclear Import: Central Dna Flaps Amentioning
confidence: 99%
“…The resulting doublestranded DNA fragment, corresponding to unintegrated 'orphan' LTR sequences, has actually been detected in HIV-1 infected cells (Li eta]., 1993). A similar DNA fragment was also detected in cells infected by spumaviruses (Kupiec et al, 1988;Renshaw eta]., 1991;Tobaly ef al., 1991).…”
Section: The ' Gap 'mentioning
confidence: 69%
“…In contrast, lenti-and spumaviruses establish productive infections with a high quantity of linear unintegrated DNA (lyric-like cycle). However, for MW and the spumaviruses, the integrated proviral state is, if it ever exists, very difficult to detect (Harris et al, 1981;Kupiec et al, 1988). Recently, it has been shown that spumaviruses encapsidate DNA molecules and replicate through an unusual pathway reminiscent of hepadnaviruses (Yu et al, 1996).…”
Section: The ' Gap 'mentioning
confidence: 99%